Effect of Carbon Diffusion on Friction and Wear Behaviors of Diamond-Like Carbon Coating Against Cr-Plating in Boundary Base Oil Lubrication - Kouami Auxence Melardot Aboua; Noritsugu Umehara; Hiroyuki Kousaka; Takayuki Tokoroyama; Motoyuki Murashima; Yutaka Mabuchi; Tsuyoshi Higuchi; Masahiro Kawaguchi (Tribology Online, 2018)
Investigations on tribological behaviors of Diamond-like Carbon (DLC) coating against other materials are strongly needed for scientific and industrial purposes. Recently, carbon diffusion has been found to play a key role in the wear of hydrogenated amorphous carbon (a-C:H) DLC coating when it is rubbed against steel counterpart material in boundary lubrication. Chromium has been reported to decrease carbon diffusion due to increase of the activation energy. In this research, we investigated on the effects of carbon diffusion on friction and wear properties of a-C:H coating when rubbed against Cr plating material. Results show that compared to steel counterpart, a-C:H coating exhibits lower friction coefficient, lower wear rate, and lower carbon diffusion rate when rubbed against Cr plating counterpart.